Cxcl8b and Cxcr2 Regulate Neutrophil Migration through Bloodstream in Zebrafish - Constanza Zuñiga-Traslaviña; Karina Bravo; Ariel E. Reyes; Carmen G. Feijóo (Journal of Immunology Research)
Neutrophils play an essential role during an inflammatory response, which is dependent on their rapid recruitment from the bone marrow to the vasculature. However, there is no information about the molecular signals that regulate neutrophil entry to circulation during an inflammatory process in humans. This is mainly due to the lack of a suitable model of study that contains similar set of molecules and that allows in vivo analyses. In this study, we used the zebrafish to assess the role of Cxcl8a, Cxcl8b, and Cxcr2 in neutrophil migration to blood circulation after injury. Using Tg(BACmpx:GFP)i114 transgenic embryos and two damage models (severe and mild), we developed in vivo lack of function assays. We found that the transcription levels of cxcl8a, cxcl8b, and cxcr2 were upregulated in the severe damage model. In contrast, only cxcr2 and cxcl8a mRNA levels were increased during mild damage. After knocking down Cxcl8a, neutrophil quantity decreased at the injury site, while Cxcl8b decreased neutrophils in circulation. When inhibiting Cxcr2, we observed a decrease in neutrophil entry to the bloodstream. In conclusion, we identified different functions for both Cxcl8 paralogues, being the Cxcl8b/Cxcr2 axis that regulates neutrophil entry to the bloodstream, while Cxcl8a/Cxcr2 regulates the migration to the affected area.